STRUCTURAL COMPOSITION OF A DOUBLE BACKFOLD IN A GROUP OVER THE BARS ON PARALLEL BARS, PERFORMED FROM VARIOUS STARTING POSITIONS OF THE FLIGHT PART - Zagrevsky, O.I.; Zagrevsky, V.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the structural composition of the studied gymnastic exercises. Methods and structure of the study. In the course of scientific work, the following were carried out: video recording of exercises, computational models for analyzing the movements of biomechanical systems, system-structural analysis of motor actions. The subject of the study is the technique of gymnastic exercises in the unsupported and in the support periods based on the materials of optical registration of movements. Results and conclusions. The sequence of changes in the phase composition in the studied gymnastic exercises is the same, and the parameters of biomechanical characteristics in the phases of movement are different. The division (differentiation) of the athlete's motor actions into separate components (periods, stages) is biomechanically justified by the motor tasks of the exercise, and its division into smaller structural parts (phases) is determined by the criterion of changing the unidirectional change in the angle in certain joints of the athlete. In complex gymnastic exercises, preparatory, basic and final actions can refer not only to the entire exercise as a whole, but also to its individual phases.